2011
DOI: 10.1063/1.3647503
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on p-type lithium niobate crystals

Abstract: Till now it is difficult to obtain a p-type lithium niobate crystal. Here the carrier types in various doped and oxidized LiNbO3 crystals have been investigated by holographic technique. The experimental results show tetravalent ions (Zr4+ and Hf4+) with doping concentrations just above optical damage resistant thresholds is helpful to increase the concentration of holes. And 3.0 mol% ZrO2 doped LiNbO3 can be used as a p-type crystal. The dominant carrier of iron doped LiNbO3 crystal can be changed to holes wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For LiNbO 3 and LiTaO 3 , n‐type semiconducting properties were obtained using reducing treatments, and by doping crystals with Fe or Cu . While p‐type semiconductor properties of LiNbO 3 and LiTaO 3 were measured in Li‐deficient LN films grown by PLD or with Zr 4+ or Hf 4+ ion doping . Innovative ferroelectronic designs can be made by utilizing and studying the charged domain walls or current leakages .…”
Section: Physical Properties and Targeted Applicationsmentioning
confidence: 99%
“…For LiNbO 3 and LiTaO 3 , n‐type semiconducting properties were obtained using reducing treatments, and by doping crystals with Fe or Cu . While p‐type semiconductor properties of LiNbO 3 and LiTaO 3 were measured in Li‐deficient LN films grown by PLD or with Zr 4+ or Hf 4+ ion doping . Innovative ferroelectronic designs can be made by utilizing and studying the charged domain walls or current leakages .…”
Section: Physical Properties and Targeted Applicationsmentioning
confidence: 99%
“…Holographic characteristics of these samples in the UV-visible range were investigated by two-wave mixing in transmission geometry at the wavelength of 351, 473 and 532 nm provided by an Ar + laser and continuous wave frequency-doubled solid-state lasers, respectively [24,25]. The experimental setup is illustrated schematically in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…However, great progress has been made in recent years to modify the electrical properties of LiNbO3. For example, p-type LiNbO3 could be obtained by doping the crystal with Zr 4+ , which, combined with the general ntype LiNbO3, provides a possibility to fabricate p-n junction based on LiNbO3 [4]. It was reported that the electric conductivity in the domain wall region was greatly increased in LiNbO3, which is very promising in the application of nanoscale electronics [5,6].…”
Section: Introductionmentioning
confidence: 99%